2018
DOI: 10.1182/bloodadvances.2017013698
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of [18F]fluorodeoxyglucose in initial positron-emission tomography predicts survival in MALT lymphoma

Abstract: The role of [F]fluorodeoxyglucose (FDG) positron-emission tomography (PET) in mucosa-associated lymphoid tissue (MALT) of marginal zone lymphoma remains poorly defined. We correlated initial PET with pathology, clinical factors, and outcome. From January 2001 to July 2012, 173 MALT lymphoma patients with a biopsied lesion identified on PET within 90 days of tissue biopsy were analyzed. PET positivity and intensity of FDG uptake were correlated with clinical factors and patient outcome. Among 173 accrued cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
2
22
1
Order By: Relevance
“…Although FDG uptake during PET-CT is frequently observed in many MALT lymphomas with high-grade malignant potential [7], this case did not show abnormal FDG uptake in the mesenteric lymph nodes or in other lesions. We removed the enlarged lymph nodes during the surgery for esophageal cancer and submitted the specimens for pathological examination.…”
Section: Discussioncontrasting
confidence: 68%
“…Although FDG uptake during PET-CT is frequently observed in many MALT lymphomas with high-grade malignant potential [7], this case did not show abnormal FDG uptake in the mesenteric lymph nodes or in other lesions. We removed the enlarged lymph nodes during the surgery for esophageal cancer and submitted the specimens for pathological examination.…”
Section: Discussioncontrasting
confidence: 68%
“…For extranodal marginal zone B cell lymphoma of the mucosa-associated lymphoid tissue (MALT lymphoma), only three studies have, so far, evaluated quantitative pretherapeutic [ 18 F]FDG/PET-derived parameters for outcome prognostication [6][7][8], probably because of the variable FDG avidity of this lymphoma subtype, due to which [ 18 F]FDG/ PET is not recommended for imaging of MALT lymphomas by the International Conference on Malignant Lymphoma (ICML) [9]. Notably, none of the these studies-including the single, very recently published study that included an evaluation of TMTV and TLG, and was unable to establish either parameter as a prognostic factor for overall survival (OS) or progression-free survival (PFS) [6]-focused on a specific treatment group, contrary to studies in other lymphoma subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some literatures indicated that few MALT lymphoma transformed into diffuse large B-cell Lymphoma (DLBCL). [27,28] Qi et al [29] reported the MALT lymphoma patients with an SUV≥10 had a higher incident rate of large cell transformation and inferior overall survival (OS). The patient in this report was diagnosed as MALT lymphoma in her parotid gland, but the PET/CT findings presented as extreme invasiveness.…”
Section: Discussionmentioning
confidence: 99%